Modification of Monoaminergic Activity by MAO Inhibitors Influences Methamphetamine Actions - Junichi Kitanaka; Nobue Kitanaka; Motohiko Takemura (AboutScience Srl, 2006)
Methamphetamine (METH) abuse is a serious health and social problem worldwide. At present, however, there are no effective medications for the treatment of METH abuse. Of the intracellular METH target proteins, monoamine oxidase (MAO) is involved in the regulation of monoaminergic tone in the brain, resulting in the modulation of METHinduced behavioral abnormalities in mammals. The METH-induced expression of increased motor activity, stereotypy, and sensitization is closely associated with monoaminergic transmission in the brain. Modifi cation of MAO activity by MAO inhibitors can influence METH action. Of the MAO inhibitors, the propargylamine derivative clorgyline, an irreversible MAO-A inhibitor, effectively blocks METH-induced hyperlocomotion and behavioral sensitization in rodents. Analysis of the associated monoaminergic activity indicates an involvement of altered striatal serotonergic transmission as well as an increased dopaminergic tone. Some effects of MAO inhibitors on METH action appear to be independent of MAO, suggesting complex mechanisms of action of MAO inhibitors in METH abuse. This review describes current research to find effective treatment for METH abuse, using MAO inhibitors.